A descriptive study of the sleeping areas of selected night shift call center agents in relation to environmental factors - Magpili, Kriselda Anica M.; Reodique Catherine C. (2011.)
This study investigated the sleeping areas of selected night shift call center agents in relation to environmental factors that affect their day time sleep. The study used Hazel Heath's (1995) theory that the environment has a significant influence on the ability to fall and remain asleep. Thus if the environmental issues can be resolved, a reduction or even elimination of sleeping problems is bound to follow (Attanasio & Bailey, 2009). The study is descriptive, using both surveys and interviews for data gathering. Using snowball sampling method, 50 respondents from Metro Manila were selected. The respondents were night shift call center agents, single, both male and female and with ownership of sleeping area. Electronic survey sheets from kwiksurveys.com and a guide interview questionnaire were used. Frequency, cluster analysis, likert scale rating, and content analysis were the treatments of data. Pie charts and tables were used to present data. It was found that the respondents, generally had sleeping problems. Both their quality and quantity of sleep were affected, which caused dissatisfaction. According to their perception, ranked from top to least, noise, not being used to daytime sleep, bright lighting, warm temperature, and uncomfortable sleeping areas were factors negatively affecting sleep. Sixty four percent (64%) of the respondents believed the environment affects sleep the most. In conclusion, simulating a night time setting for sleeping areas and providing comfortable sleeping amenities will reduce or eliminate the sleeping problems of selected night shift call center agents.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Bedrooms